(3GdJPcQI aj GdbQGAGJs - (3CHh GdMSf WGgQ Hf YHO GdefYe Hf YHjO Gddg Hf ZdHhf GdebQj,J (B380 (3g` s
(3ChdgG (B:s
(3ShQI GdCfYGe bQC CHh HcQ hLeRI hGdcSGFi hjYbhH (B( (3ef SKQa Yfg (B) (3HaJM GdjGA hcSQ GdQGA s
(3BNQgG (B:s
(3bGd MOKfG GHf eLGgO bGd MOKfG GdMSf bGd eMOKfG YcQeI Hf SdjeGf Hf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B392s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
Keywords: (3GdbQGAGJ hGdJLhjOs